2015
DOI: 10.3762/bjoc.11.220
|View full text |Cite
|
Sign up to set email alerts
|

The marine sponge Agelas citrina as a source of the new pyrrole–imidazole alkaloids citrinamines A–D and N-methylagelongine

Abstract: SummaryThe chemical investigation of the Caribbean sponge Agelas citrina revealed four new pyrrole–imidazole alkaloids (PIAs), the citrinamines A–D (1–4) and the bromopyrrole alkaloid N-methylagelongine (5). All citrinamines are dimers of hymenidin (6) which was also isolated from this sponge as the major metabolite. Citrinamines A (1) and B (2) are derivatives of the PIA dimer mauritiamine (7), whereas citrinamine C (3) is derived from the PIA dimer nagelamide B (8). Citrinamine D (4) shows an uncommon linkag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 19 publications
(20 reference statements)
0
35
0
Order By: Relevance
“…The Caribbean specimen of Agelas citrina was firstly found to yield three new diterpene alkaloids, (−)-agelasidine E ( 8 ), (−)-agelasidine F ( 9 ) and agelasine N ( 10 ) [ 9 ]. Latter chemical investigation showed that this sponge also produces four new pyrrole-imidazole alkaloids, citrinamines A–D ( 11 – 14 ), and one bromopyrrole alkaloid N -methylagelongine ( 15 ) ( Figure 5 ) [ 10 ]. Compounds 12 – 14 had antimicrobial activities whereas no inhibitory effect on cell proliferation of mouse fibroblasts was found for 11 – 14 .…”
Section: Natural Products From Agelas Genusmentioning
confidence: 99%
“…The Caribbean specimen of Agelas citrina was firstly found to yield three new diterpene alkaloids, (−)-agelasidine E ( 8 ), (−)-agelasidine F ( 9 ) and agelasine N ( 10 ) [ 9 ]. Latter chemical investigation showed that this sponge also produces four new pyrrole-imidazole alkaloids, citrinamines A–D ( 11 – 14 ), and one bromopyrrole alkaloid N -methylagelongine ( 15 ) ( Figure 5 ) [ 10 ]. Compounds 12 – 14 had antimicrobial activities whereas no inhibitory effect on cell proliferation of mouse fibroblasts was found for 11 – 14 .…”
Section: Natural Products From Agelas Genusmentioning
confidence: 99%
“…Thus, agelasidines with antifungal activity against Candida albicans have been extracted from A. citrina, one of the most promising crude extracts in the present study, and (-)-agelasidine C (MIC 0.5 mg/L) was found to be the most active [34]. More recently, new pyrrole-imidazole alkaloids (denominated citrinamines) were isolated from the same species and were found to be able to inhibit the growth of the Gram-positive bacteria Micrococcus luteus and Mycobacterium phlei [35]. Inhibition of the growth of E. coli and Pseudomonas putida by extracts of this sponge has also been reported [36].…”
Section: Animal Materials Studiesmentioning
confidence: 72%
“…[59] Four novel compounds 87-90 classified as pyrrole alkaloids containing various imidazolidine-or imidazole-derived moieties were isolated from marine sponge Agelas citrina, of which compound 88 had a unique taurine group. [60] Six new bromopyrrole alkaloids 91-96 from South China Sea sponge Agelas sp. were obtained.…”
Section: Pyrrole Alkaloidsmentioning
confidence: 99%
“…[59-65,68,69,74 -77] Most of them were collected from or near South China Sea at the depth of 30 m above [59,61,[63][64][65]68,69,[74][75][76][77] , while only the six compounds 87-90 and 97 and 98 were collected from Bahamas sea area nearby as well as the same range of depth. [60,62] The 23 alkaloids 39-44, 47-49 and 55-68 were isolated from the genus of Monanchora. They belonged to guanidine alkaloids, which took up 15.3 % of the total sponge alkaloids.…”
Section: Production Environmentmentioning
confidence: 99%